Features of group cohesion in cooperative base groups in an ESL Class - Ho, Sook Wah (1998)
The first objective of this study was to investigate if there was cohesiveness in the relationships among base group members, and if there was, to identify descriptive-interpretive features of group cohesion. The identified features contribute significantly to theory building on group cohesion. The second objective was to formulate an organising scheme which classifies the descriptive-interpretive features of group cohesion into different categories and sub-categories. This is a helpful framework for future qualitative data analysis on group cohesion. This heuristic research was worked into a regular ESL class for one semester. The researcher was also the class teacher. Seventeen first semester UPM undergraduates enrolled in a level three English proficiency course were the subjects of the study. The students were divided into four heterogeneous base groups. The main instrument for data collection was the students' journals containing their written observations of their base groups. The journal entries were analysed inductively to identify descriptive-interpretive features of group cohesion, and to formulate an organising scheme. The organising scheme was validated and revised a couple of times before it arrived at its final form. The reliability of the formulated scheme and interpretation of the cohesive features was established by computing the degree of correspondence between the raters' categorisations with the researcher's; the reliability was found to be at .87 and .91 respectively. The questionnaire was used as a secondary instrument to verify the cohesive features identified from the journals.